THE CULTURE OF PRESERVING THE QUALITY OF MEMORY OF THE QUR’AN THROUGH THE TAQSĪM AL-MAJĀLIS PROGRAM: THE STUDY OF LIVING QUR’AN IN TAHFIDZUL QUR’AN INSTITUTIONS - Yufi, Moch (Universitas Nurul Jadid, 2021)
The culture of reading the Qur’an, which is carried out together, is one of the forms of the phenomenon of Muslims reviving or presenting the Qur’an in everyday life. This culture gives special attention and becomes the main attraction for students who follow it, according to the motives and views of the students. Of course, with different social and cultural backgrounds, these students have different perceptions about this. This study uses a qualitative method with a focus on case studies. The case study obtained from the results of research with the taqsīm al-majālis program aims to regenerate a culture of reading the Qur’an and a form of responsibility for the Zaid bin Thabit area stakeholders to the students who have obtained the sanad because, in reality, when in the field even though the students have completed The Tahfidz program has reached the sanad program, but there is still a need for a program or culture to preserve the quality of memorizing the Qur’an, namely the taqsīm al-majālis program. The results of this study are: First, the procession regarding the culture of preserving the Qur’an by being packaged in a container for reading the Qur’an through the taqsīm al-majālis program; the readings are carried out every Tuesday by students who have received the Sanad al-Qur’an, this culture is a form of stakeholder idea. Second, this culture is nothing but the pursuit of complete memorization, but to train and grow the quality of memorizing the Qur’an, an appropriate strategy is still needed. Third, for the random distribution of juz readings. The motivations are the culture of preserving the quality of memorizing the Qur’an by listening as a form of evaluation of the memorization of students who have obtained the sanad, increasing enthusiasm for returning for students who have received the sanad al-Qur’an, and a motivation for students who have not yet received the sanad al-Qur’an.